3-D X-ray tomography of diamondiferous mantle eclogite xenoliths, Siberia: A review. (1st April 2015) - Howarth, Geoffrey H.; Sobolev, Nikolay V.; Pernet-Fisher, John F.; Ketcham, Richard A.; Maisano, Jessica A.; Pokhilenko, Lyudmila N.; Taylor, Dawn; Taylor, Lawrence A.
Abstract: Diamonds form over billions of years, hundreds of kilometers beneath the Earth's surface, and in combination with inclusions trapped within, provide important constraints on the evolution of the mantle over geological time. Diamonds are generally studied as individual crystals sourced from highly explosive kimberlite pipes, which entrain and subsequently disaggregate mantle fragments (xenoliths) en route to the surface. This has resulted in a general absence of robust textural descriptions of diamonds relative to their hosting mantle protolith. The textural associations of diamonds within their mantle host rocks are reviewed here on the basis of a compilation of X-ray tomographic data for 17 diamondiferous eclogite xenoliths from Siberian kimberlites. This review represents a comprehensive description of diamonds relative to their host silicates. The lack of such descriptions in previous studies is largely due to the rarity of these xenoliths, the difficulty in preparing petrographic thin sections containing diamonds, and their high-monetary value. High-resolution computed X-ray tomography (HRCXT) produces up to 1200 sequential 2-D slices through individual xenoliths, each of which represents a 'pseudo thin-section' with a resolution on the order of 5–20 μm. The improved resolution of X-ray imaging in recent studies allows for the identification of not only primary minerals, but metasomatic minerals assemblages, including: 'spongy' textured clinopyroxene, phlogopite/K-richterite, and hercynitic spinel, allowing for the delineation of distinct metasomatic pathways through the xenoliths and their relationship to diamonds. Diamonds are observed in three distinct textural settings, potentially representing several temporally distinct diamond growth events, these setting includes: (1) diamonds completely enclosed in garnet; (2) diamonds associated with highly embayed silicate grain boundaries; and (3) diamonds contained within distinct metasomatic 'plumbing-systems'. Diamonds observed completely enclosed in garnets suggest an early diamond-forming event prior to major re-crystallization and eclogite formation during subduction. The occurrence of diamond in association with embayed garnets suggests that diamond grew at the expense of the hosting silicate protolith. In addition, the spatial relationships of diamonds with metasomatic pathways, which are generally interpreted to result from late-stage proto-kimberlitic fluid percolation, indicate a period of diamond growth occurring close to, but prior to, the time of kimberlite emplacement. Furthermore, the paragenesis of sulfides within eclogite xenoliths are described using 3-D models for entire xenoliths volumes, providing important constraints of the timing of sulfide mobilization within the mantle. Three-D animations created using X-ray tomography data for ten of the xenoliths can be viewed at the following link:http://eps.utk.edu/faculty/taylor/tomography.php .